2023
DOI: 10.1186/s41687-023-00628-1
|View full text |Cite
|
Sign up to set email alerts
|

Health and well-being of the Portuguese citizens: impacts of the COVID-19

Lara N. Ferreira,
Luís N. Pereira,
Pedro L. Ferreira

Abstract: Background COVID-19 pandemic placed unprecedented pressure on societies and healthcare systems around the world. Over the last years, measures imposed in almost all countries dealing with the pandemic sent the entire world into an extensive crisis and thus into a deep global recession. Since the outbreak began, many European countries have faced three/four waves of pandemic. Portugal has mainly dealt with three waves (March/April’2020; October/November’2020; January/February’2021), the third be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Lockdowns started to be implemented worldwide to mainly contain deaths and prevent healthcare systems from becoming overwhelmed and thus hampered from helping those in need [ 3 ]. However, this approach had profound consequences on people’s lives [ 4 , 5 ], namely negative social and economic impacts [ 4 – 6 ]. A study compared the health-related quality of life (HRQoL) of Portuguese citizens during the COVID-19 pandemic to pre-COVID-19 (data between November 2015 and January 2016) and found that HRQoL decreased during the pandemic [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lockdowns started to be implemented worldwide to mainly contain deaths and prevent healthcare systems from becoming overwhelmed and thus hampered from helping those in need [ 3 ]. However, this approach had profound consequences on people’s lives [ 4 , 5 ], namely negative social and economic impacts [ 4 – 6 ]. A study compared the health-related quality of life (HRQoL) of Portuguese citizens during the COVID-19 pandemic to pre-COVID-19 (data between November 2015 and January 2016) and found that HRQoL decreased during the pandemic [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach had profound consequences on people’s lives [ 4 , 5 ], namely negative social and economic impacts [ 4 – 6 ]. A study compared the health-related quality of life (HRQoL) of Portuguese citizens during the COVID-19 pandemic to pre-COVID-19 (data between November 2015 and January 2016) and found that HRQoL decreased during the pandemic [ 4 ]. Furthermore, not only HRQoL but also cancellation or postponement of medical appointments differed between sex, age groups and economic levels [ 4 ] Rearrangements related to household configuration also happened as a way to cope with restrictions, namely young adults moving to their parents’ house [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation